Effect of metal type and surface treatment on shear bond strength of resin cement (in vitro study) - Hiba Al-Helou; Eyad Swed (Wolters Kluwer Medknow Publications, 2016)
Background: Resin-bonded fixed partial dentures appeared to prevent the excessive preparation of dental tissue. Investigation of surface treatments to improve the bond of resin cements to metals may contribute to the longevity of these restorations. Due to the potential lack of ideal preparation form, the type of alloy and its surface pretreatment may have clinically relevant correlations with the retentive strength of castings to minimally retentive preparations. Aim: The aim of this search is to study the bonding resin cement strength to different types of the metal alloy due to the surface treatment. Purpose: Evaluate the effects of two different surface treatments on shear bond strength (SBS) between a palladium-silver alloy (Pb-Ag) and commercially pure titanium (CP Ti) cast alloy with resin luting cements. Materials and Methods: A total of 120 cylinders having 5 mm in diameter and 4 mm in height were divided into two different main groups of metal type: 60 cylinders cast from CP Ti Grade I (Tritan - Reintitan - Germany-Dentaurum) as a base metal and 60 cylinders cast from Pb-Ag (Status-Yamakin, Japan) as a noble metal. 30 cylinders from each type were embedded in acrylic resin, and the rest were left without embedded in acrylic resin. All of the cylinders were smoothed with silicon carbide papers and sandblasting with 50-μm aluminum oxide. Specimens of each metal type were divided into two subgroups, which received one of the following luting techniques: (1) Multilink (Ivoclar Vivadent), (2) Multilink (Ivoclar Vivadent) plus metal zirconia primer (MZP). Every two cylinders from the same metal type and surface treatment were bonded to each other. All specimens were stored in distilled water at 37°C for 24 h and then thermal cycled (500 cycles, 5-55°C). After thermal cycling, the specimens were stored in 37°C distilled water for an additional 24 h before being tested in shear strength. Data (MPa) were analyzed using T-s tests to study the significance of various - means among groups and perform a comparison between each two groups of them. Results: The T-s tests indicated significant effect of combination of the sandblasting technique (aluminum oxide particles 50 μm) with the application of primer MZP before using resin cement (P < 0.05) independent of the metal type used. The metal type did not significantly affect SBS for any of the compared surface pretreatments. Conclusion: Metal primer application significantly enhanced SBS to base and a noble metal. No significant differences in shear strength were found between alloys.